2004
DOI: 10.1063/1.1805197
|View full text |Cite
|
Sign up to set email alerts
|

Increased terahertz emission from thermally treated GaSb

Abstract: We report on the terahertz (THz) emission from GaSb surfaces with modified surface stochiometry. While very weak emission is observed from virgin GaSb wafers, the emission is significantly increased by a single thermal treatment of the wafers. Optimum emission is observed for 500°C thermal annealing. The reason for the THz emission is a surface electric field induced by thermal decomposition of the surface, as corroborated by Raman spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Raman scattering can give effective information about various crystalline structures from single crystalline to amorphous samples. A number of Raman studies on single crystalline GaSb samples have been reported [9,10,11]. A two-mode behaviour was found for this alloy composition, and TO-LO splitting of both GaSb-like and A1Sb-like modes could not be resolved in the high-resolution first-order Raman spectra.…”
Section: Introductionmentioning
confidence: 86%
“…Raman scattering can give effective information about various crystalline structures from single crystalline to amorphous samples. A number of Raman studies on single crystalline GaSb samples have been reported [9,10,11]. A two-mode behaviour was found for this alloy composition, and TO-LO splitting of both GaSb-like and A1Sb-like modes could not be resolved in the high-resolution first-order Raman spectra.…”
Section: Introductionmentioning
confidence: 86%
“…GaAs, [1][2][3][4][5][6][7] GaSb, 2,4,8,9 InN, [10][11][12] InP, 2,4,13,14 InAs, [4][5][6]11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and InSb 15,17,[31][32][33] have demonstrated emission of subpicosecond terahertz-radiation pulses upon irradiation with femtosecond near-infrared laser pulses. This type of terahertz radiation source has enabled the development of time-domain terahertz spectroscopy and terahertz imaging over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Free-space pulsed terahertz (THz) radiation can be generated by the motion of photo-excited electrons and holes that are accelerated by the local or bias field which may be an external applied field or an internal field in charge depletion layers resulting from the charge transfer due to a Schottky contact and a p-n junction, etc. [1][2][3]. The amplitude of the THz radiation is widely believed to be proportional the local or bias field, loc E , as well as the number of photoexcited carriers n ph .…”
Section: Introductionmentioning
confidence: 99%